PENGARUH GREEN ACCOUNTING MELALUI PENGELOLAAN LIMBAH DAN EFISIENSI ENERGI TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Sulistiyana, Fitri; Trihastuti, Adiati (Jurnal Manajemen dan Bisnis, 2025)
This research is conducted to analyze the impact of Green Accounting implementation through Waste Management and Energy Efficiency on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Green Accounting has become an important focus in the business world as it integrates environmental aspects into corporate financial reporting to support business sustainability. This study uses a quantitative research method and secondary data obtained from the financial statements and sustainability reports of manufacturing companies in the consumer goods sub-sector listed on the IDX for the period 2020-2023. The independent variable (X) used is Green Accounting, measured through waste management and energy efficiency, while the dependent variable is financial performance, measured using Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Data is analyzed using the Partial Least Squares (PLS) method. The results of the research show that the implementation of Green Accounting through waste management and energy efficiency has a significant impact on the company's financial performance. Effective waste management can reduce operational costs and enhance the company's reputation, while energy efficiency helps lower production costs and increase profitability. This study provides practical implications for companies to not overlook environmental aspects in business operations to achieve better financial performance while supporting sustainable development.